2011
DOI: 10.1111/j.1365-2958.2011.07650.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulators of the GAD acid stress island are carried by effector protein‐encoding prophages and indirectly control type III secretion in enterohemorrhagic Escherichia coli O157:H7

Abstract: SummaryType III secretion (T3S) plays a pivotal role in the colonization of ruminant hosts by Enterohemorrhagic Escherichia coli (EHEC). The T3S system translocates effector proteins into host cells to promote bacterial attachment and persistence. The repertoire and variation in prophage regions underpins differences in the pathogenesis and epidemiology of EHEC strains. In this study, we have used a collection of deletions in cryptic prophages and EHEC O157 O-islands to screen for novel regulators of T3S. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 56 publications
1
78
1
1
Order By: Relevance
“…RNA-seq analysis revealed that deletion of grvA leads to the upregulation of gadE, a known transcriptional repressor of LEE-encoded regulator ler (52,53). As such, the contribution of gadE to GrvA-dependent control of the LEE and adherence to cultured intestinal epithelial cells was examined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA-seq analysis revealed that deletion of grvA leads to the upregulation of gadE, a known transcriptional repressor of LEE-encoded regulator ler (52,53). As such, the contribution of gadE to GrvA-dependent control of the LEE and adherence to cultured intestinal epithelial cells was examined.…”
Section: Resultsmentioning
confidence: 99%
“…GadE is a negative regulator of LEE expression, acting directly on the LEE1 promoter to repress ler transcription (52,53). In the preceding experiments, the upregulation of ler by GrvA was determined to correspond with gadE repression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we and others showed that the prototypical EHEC O157:H7 strain, EDL933, carries three prophage-encoded loci, patE, psrA, and psrB, which encode AraC-like transcriptional regulators that downregulate the expression of the LEE-en-coded type III secretion pathway (24,25). Our previous work also demonstrated that PatE is involved in transcriptional activation of AR pathways of strain EDL933 (24).…”
mentioning
confidence: 94%